THE ANALYSIS SPEECH ACTS OF THE MAIN CHARACTER IN FREEDOM WRITERS MOVIE SCRIPT - Mulyani, Upit; Latifah, Dewi (PROJECT (Professional Journal of English Education), 2018)
Abstract In the study of language, what people do by saying something is called speech acts. Speech acts are not only found in everyday life but also in the film. This research concerns with speech acts produced by the main character in Freedom Writers movie script. The aims of this research are to describe the types of speech acts and to analyze the most dominant speech acts produced by the main character. Besides, the aims of this research are also to know and describe the purposes of Erin Gruwell as the main character to use speech acts. Austin’s (1962) theory of speech acts is applied in this research as the major theory. This research is qualitative research. The subject of this research is texts in the form of movie script and document analysis is used to gather the data. Qualitative research is applied to analyze the data in the form of the text. There are 100 utterances to be analyzed. The result of this research shows that the five types of speech acts produced by Gruwell are representatives, directives, expressives, commissives and declarative. This study shows that the dominant speech acts used is representatives and it reaches 58%. It indicates that Gruwell uses representative because  she wants to express what she really knows.